2008
DOI: 10.1016/j.febslet.2008.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast nitrite uptake is enhanced in Arabidopsis PII mutants

Abstract: In higher plants, the PII protein is a nuclear-encoded plastid protein that regulates the activity of a key enzyme of arginine biosynthesis. We have previously observed that Arabidopsis PII mutants are more sensitive to nitrite toxicity. Using intact chloroplasts isolated from Arabidopsis leaves and 15 N-labelled nitrite we show that a light-dependent nitrite uptake into chloroplasts is increased in PII knock-out mutants when compared to the wild-type. This leads to a higher incorporation of 15 N into ammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…From these results, a regulatory role of PII in the fine-tuning of fatty acid biosynthesis and partitioning in seeds had been inferred (Baud et al 2010). Furthermore, in A. thaliana PII mutants, nitrite uptake in chloroplast is enhanced (Ferrario-Mery et al 2008), resembling the regulatory defect of nitrite/nitrate uptake in cyanobacterial PII mutants (Kloft and Forchhammer 2005). Altogether, the data indicate that during the evolution of plastids, PII lost its primary function of coordinating gene expression through interactions with PipX, but preserved its role in nitrogen (arginine) storage metabolism, and eventually took over fine-tuned regulation of carbon (fatty acid) storage metabolism.…”
Section: Further Functions Of Pii Signaling In Oxygenic Phototrophsmentioning
confidence: 88%
“…From these results, a regulatory role of PII in the fine-tuning of fatty acid biosynthesis and partitioning in seeds had been inferred (Baud et al 2010). Furthermore, in A. thaliana PII mutants, nitrite uptake in chloroplast is enhanced (Ferrario-Mery et al 2008), resembling the regulatory defect of nitrite/nitrate uptake in cyanobacterial PII mutants (Kloft and Forchhammer 2005). Altogether, the data indicate that during the evolution of plastids, PII lost its primary function of coordinating gene expression through interactions with PipX, but preserved its role in nitrogen (arginine) storage metabolism, and eventually took over fine-tuned regulation of carbon (fatty acid) storage metabolism.…”
Section: Further Functions Of Pii Signaling In Oxygenic Phototrophsmentioning
confidence: 88%
“…Intact rosette leaf chloroplasts were Percoll-purified as described in ref. 24. The plants were maintained in darkness during 24 h to reduce starch levels and minimize chloroplast damage, and were subsequently transferred to light (150 μE·m Expression and Purification of Recombinant Proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of a PII-NAGK complex has been solved for Arabidopsis (22) and Synechococcus elongatus proteins (23). It is possible that the function of plant PII has further similarities to those found in cyanobacteria because it has been proposed that plant PII regu-lates chloroplast nitrite uptake via an interaction with a nitrite transporter (24).…”
mentioning
confidence: 99%
“…In higher plants, the PII protein regulates arginine biosynthesis 5 and plays a role in nitrogen regulation. 6 We analyzed the proteins enriched in GO biological process; it was found that the P-II nitrogen sensing protein possessed multifarious functions, such as biological regulation, regulation of biological quality, response to disaccharide stimulus, cellular homeostasis, aromatic compound biosynthetic process, and phenylpropanoid metabolic process (Fig.…”
mentioning
confidence: 99%
“…It has been reported that chloroplast nitrite uptake was enhanced in Arabidopsis PII knockout mutants. 5 The downregulation of P-II nitrogen sensing protein under salt stress probably increase nitrite uptake and nitrogen metabolism. Considering the accumulation of amino acids under stress, 1 the increased P-II nitrogen sensing protein might contribute to synthesis of amino acids, such as proline and non-protein amino acid g-aminobutyric acid (GABA) which play important roles in scavenging ROS and stabilizing the structure of proteins.…”
mentioning
confidence: 99%